Design of functional polymeric materials for cancer-targeted drug delivery and cellular capture and isolation - Radaha, Esther L. (Kansas State University, 2021)
Synthetic polymeric materials offer many exciting advantages with the plethora of functionalization techniques affording materials with unique properties, multiple functionalities, and elaborate architectures for a variety of applications. In the drug delivery field, the use of synthetic polymers as nano-sized drug carriers in cancer nanomedicine has gained tremendous interest as an alternative to conventional small molecule anticancer drugs to reduce drug-related toxicity and increase targetability. Like other nanocarriers, synthetic polymeric nanocarriers rely on passive-drug targeting, also known as the Enhanced Permeability and Retention (EPR) effect in leaky tumor vasculature for delivery of therapeutics. The biological complexity and barriers that exist in the body however have proven to be a huge challenge in selectively delivering therapeutics to cancer cells. Synthetic polymers also offer significant advantages for improved isolation and characterization of microbes attached to surfaces compared to conventional techniques. However, the retrieval of microbes from synthetic polymer interfaces with high spatial precision without damaging the underlying live bacterial cells remains a critical challenge for further characterization. Therefore, the goal of this dissertation is to explore and develop synthetic, functional, stimulus-responsive polymeric interfaces (polymeric micelles, photodegradable hydrogels) for targeted drug delivery to cancer cells and improved isolation of microbes for molecular characterization. The majority of this thesis (chapters 2, 3, and 4) focuses on utilizing the intrinsic properties present in tumor microenvironments (TME), mainly elevated levels of reactive oxygen species (ROS) and overproduction of matrix metalloproteinase-2 (MMP-2) enzyme for the design and synthesis of stimuli-sensitive synthetic block copolymer polymeric micelles (BCPMs) by reversible addition-fragmentation chain transfer (RAFT) polymerization for targeted delivery of therapeutics to cancer cells. The synthesized BCPMs were extensively studied and evaluated for their chemistry and biological functions in in vitro cancer therapy. In chapter 2, the conventional chemotherapeutic drug, Doxorubicin (DOX) was loaded physically into the hydrophobic core of BCPMs bearing a library of oxidation-sensitive thioether groups. Results showed that the micelles, especially micelles with intermediate ROS sensitivity, significantly increased toxicity of DOX in liver cancer cells (HepG2) but protected normal cells, human umbilical endothelial cells (HUVECs) from DOX cytotoxicity. Taking it a step further, in chapter 3, hydrogen sulfide (H₂S) prodrug (ADT) was chemically conjugated to the core of BCPMs bearing oxidation-sensitive thioether group and the anti-cancer effects of H₂S in colon cancer cells (HT29) were evaluated. A greater anti-proliferative effect was observed in HT29 cells with no significant toxicity in HUVEC cells. In chapter 4, a different approach was taken where BCPM bearing MMP-2 enzyme cleavable peptide motifs and chemically conjugated ADT was designed for site-specific delivery of H₂S to cancer cells. The greater release of H₂S from MMP-2 sensitive micelles exhibited stronger anti-proliferative activity in HT29 cells. The final portion of this thesis (chapter 5) focuses on the development of the polymer surface dissection (PSD) method which uses biofunctionalized, photodegradable polyethylene glycol (PEG)-based hydrogels for the isolation of microbes from polyvinylidene difluoride wastewater membrane surfaces. The flocs were extracted with high spatial precision and minimal DNA damage after exposure to spatiotemporally controlled ultraviolet (UV) light using a patterned illumination tool, allowing for follow-up characterization by 16S rRNA sequencing. The technique allows for the identification of microbes that form small flocs on membrane surfaces without requiring a culture step for enrichment, and will be used in future work to identify communities of microorganisms that initiate membrane biofilms in bio-separation processes.
Keywords: Drug delivery; Cancer; Polymeric micelles; Hydrogen sulfide; Biofouling; Polymer surface dissection